Pelatihan Pemanfaatan Perangkat Lunak â€œMind Own Your Businessâ€ (MYOB)- For Accounting V.25 Sebagai Media Pembukuan Pada Toko One Bangunan Kelurahan Bandar Buat Kota Padang - Maretha Rissi, Dita; Hatta, Ermatati; Oliyan, Fitra; Amelia Herman, Lisa (Jurusan Akuntansi Politeknik Negeri Padang, 2020)
Toko One Bangunan is located at Jalan Gadut, Bandar Subdistrict, for 6 employees. Toko One Bangunan was a family business and now has several branches in the city of Padang, but the responsibility has been given to each child. So that the shop in Gadut is held by Mr. Alfi. To be able to find out business results and conduct business analysis, financial reports or business results reports through bookkeeping are sufficient and suitable for business lines. However, the One Bangunan store business which is managed by Mr. Alfi has not carried out adequate financial accounting in accordance with MSME-based records. Mr. Alfi only has 1 small book which is used as a record of incoming money per day. So it will be difficult for business owners to know the development of this business and also not be able to make proper economic decisions because no financial reports are produced as the basis for the analysis. This condition is also related to the closure of Mr. Alfi's furniture business, which was established in 2009. One of the reasons for this is the closure of the furniture business because there is no bookkeeping. Meanwhile, for every sale, there are some customers who do not immediately pay in cash. So it is difficult for owners to monitor customers who have not paid off their obligations. The purpose of this activity is to help the One Bangunan store business to book its business using Mind Your Own Business (MYOB) for Accounting V.25 software which is very suitable for this type of business to apply. The software offered is very simple to use by beginners and can generate financial reports automatically from the transactions that have been inputted. So that with this computerized bookkeeping can help work quickly and accurately, later business owners can use these financial reports as study material to analyze their business and be able to maintain their business in the future.